International journal of mineral processing (Elsevier, 1974)
"The International journal of mineral processing covers all aspects of the processing of solid-mineral materials such as metallic and non-metallic ores, coals and other solid sources of secondary materials, etc. Topics dealt with include: comminution, sizing, classification (in air and water), gravity concentration, flotation, electric and magnetic separation, miscellaneous physical separation techniques, mixing and blending, thickening, filtering, drying, storage, transport, agglomeration, pyrometallurgy and hydrometallurgy (when applied to low-grade raw materials), biohydrometallurgy (when applied to low-grade raw materials), biometallurgy (use of bacteria and other living organisms), testing, control and automation, waste treatment and disposal and mineralogical studies (when related to beneficiation)."
Keywords: Ore-dressing : Periodicals